Pemanfaatan Limbah Praktikum Laboratorium Mikrobiologi Menjadi Pupuk Cair dan Ecoenzim - Renardi Erwinsyah Putra; Mutaufiq Mutaufiq; Ratih Nirmala Dewi (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Microbiology laboratory waste such as residual growth media (Nutrient Agar, Nutrient Broth, Azotobacter and Rhizobium growth media) has the potential to be processed into products of economic value. This study aims to analyze the utilization of microbiology practice waste into Liquid Organic Fertilizer (POC) and ecoenzymes. The research method includes collecting, grouping, and product manufacturing trials using 9.4 kg of solid waste and 11.56 liters of liquid waste. Liquid waste is processed into POC, POC Rhizobium, Azotobacter using a mixture of molasses and EM4 (1:1), with an incubation period of 7–30 days. Solid waste is processed into ecoenzymes with a molasses:substrate:water ratio (1:3:10) for 90 days, as well as fermentation of maggot feed. The results of the study demonstrated the effectiveness of laboratory waste utilization, yielding 36.17 liters of general fertilizer (POC), 1.2 liters of Rhizobium fertilizer (POC), 2.3 liters of Azotobacter fertilizer (POC), 12 liters of ecoenzyme, and 1 kg of maggot feed. This research demonstrates that proper laboratory waste management can produce products applicable to agriculture.